Bioinspired Rhamnolipid Protects Wheat Against Zymoseptoria tritici Through Mainly Direct Antifungal Activity and Without Major Impact on Leaf Physiology - Platel, Rémi; Lucau-Danila, Anca; Baltenweck, Raymonde; Maia-Grondard, Alessandra; Chaveriat, Ludovic; Magnin-Robert, Maryline; Randoux, Béatrice; Trapet, Pauline; Halama, Patrice; Martin, Patrick; Hilbert, Jean-Louis; Höfte, Monica; et al. (Frontiers in Plant Science, 2022)
Rhamnolipids (RLs), glycolipids biosynthesized by the Pseudomonas and Burkholderia genera, are known to display various activities against a wide range of pathogens. Most previous studies on RLs focused on their direct antimicrobial activity, while only a few reports described the mechanisms by which RLs induce resistance against phytopathogens and the related fitness cost on plant physiology. Here, we combined transcriptomic and metabolomic approaches to unravel the mechanisms underlying RL-induced resistance in wheat against the hemibiotrophic fungus Zymoseptoria tritici, a major pathogen of this crop. Investigations were carried out by treating wheat plants with a bioinspired synthetic mono-RL with a 12-carbon fatty acid tail, dodecanoyl α/β-L-rhamnopyranoside (Rh-Est-C12), under both infectious and non-infectious conditions to examine its potential wheat defense-eliciting and priming bioactivities. Whereas, Rh-Est-C12 conferred to wheat a significant protection against Z. tritici (41% disease severity reduction), only a slight effect of this RL on wheat leaf gene expression and metabolite accumulation was observed. A subset of 24 differentially expressed genes (DEGs) and 11 differentially accumulated metabolites (DAMs) was scored in elicitation modalities 2, 5, and 15 days post-treatment (dpt), and 25 DEGs and 17 DAMs were recorded in priming modalities 5 and 15 dpt. Most changes were down-regulations, and only a few DEGs and DAMs associated with resistance to pathogens were identified. Nevertheless, a transient early regulation in gene expression was highlighted at 2 dpt (e.g., genes involved in signaling, transcription, translation, cell-wall structure, and function), suggesting a perception of the RL by the plant upon treatment. Further in vitro and in planta bioassays showed that Rh-Est-C12 displays a significant direct antimicrobial activity toward Z. tritici. Taken together, our results suggest that Rh-Est-C12 confers protection to wheat against Z. tritici through direct antifungal activity and, to a lesser extent, by induction of plant defenses without causing major alterations in plant metabolism. This study provides new insights into the modes of action of RLs on the wheat-Z. tritici pathosystem and highlights the potential interest in Rh-Est-C12, a low-fitness cost molecule, to control this pathogen.